2014
DOI: 10.1093/nar/gku742
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium RbpA cooperates with the stress-response σB subunit of RNA polymerase in promoter DNA unwinding

Abstract: RbpA, a transcriptional activator that is essential for Mycobacterium tuberculosis replication and survival during antibiotic treatment, binds to RNA polymerase (RNAP) in the absence of promoter DNA. It has been hypothesized that RbpA stimulates housekeeping gene expression by promoting assembly of the σA subunit with core RNAP. Here, using a purified in vitro transcription system of M. tuberculosis, we show that RbpA functions in a promoter-dependent manner as a companion of RNAP essential for promoter DNA un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(91 citation statements)
references
References 43 publications
6
85
0
Order By: Relevance
“…1C), confirming previous sequencebased structural predictions (15)(16)(17). Four residues of 15-residue RbpA-BL connecting the RbpA-SID to the RCD are also visible in the structure.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1C), confirming previous sequencebased structural predictions (15)(16)(17). Four residues of 15-residue RbpA-BL connecting the RbpA-SID to the RCD are also visible in the structure.…”
Section: Resultssupporting
confidence: 86%
“…Adding favorable protein/DNA contacts to the transcription initiation complex would potentially stabilize a transcription initiation intermediate, which is consistent with findings that RbpA activates transcription primarily by stimulating RPo formation (15,17). The role of RbpA-R79, which structural modeling predicts could contact the nt-strand DNA phosphate backbone at the −14 position (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additional contacts between RbpA and RNAP ␤ have been proposed based on cross-linking experiments (63, 73,74), but the recent structural modeling of RbpA onto an RNAP-promoter open complex would be incompatible with these interactions (71), suggesting that further analysis will be needed to resolve these inconsistencies. RbpA has been shown to increase the affinity of the factor to the core RNAP, increase the affinity of RNAP holoenzyme to promoter DNA, and facilitate the formation of RP o (71,75,76), all of which could contribute to the ability of RbpA to promote RNAP-promoter complex formation and stability. The housekeeping factor A has been reported to have an affinity for M. tuberculosis RNAP core enzyme similar to that of the alternative factor F (74), in which case RbpA may be necessary to improve A affinity and competitiveness for RNAP under conditions that require the activity of A .…”
Section: Factors: the Generals Of Stress Responsesmentioning
confidence: 99%
“…The initiation factors are positioned near the upstream edge of the transcription bubble. 43,44 Techniques such as fluorescent labeling were used to study the open complex using M. bovis RNAP which is known to form open complexes that are more unstable as compared to E.coli RNAP. It was found that the initiation factors act independently and cooperatively to regulate transcription and that only in the presence of both factors does the transcription kinetics in mycobacteria appear to be similar to that observed in E. coli.…”
Section: Mycobacterium Tuberculosis: a Closer Lookmentioning
confidence: 99%